The Berkeley DB Book - Himanshu, Yadava (Apress, 2013)
The database technology landscape has been changing rapidly over the last few years. The server-based relational databases, which were so successful in solving the data-storage problem for traditional client/server and web-based applications, are no longer able to meet the requirements of newer applications, such as handheld devices, appliance-based solutions, and distributed applications. Berkeley DB is not a new technology that was designed to meet the requirements of this new breed of applications, but it is flexible enough to be used in these applications nevertheless. Berkeley DB doesn’t fulfill all the requirements of these applications, so new database technologies will evolve to fill the void. However, its versatility and flexibility will certainly influence the design of any new database product.